2013
DOI: 10.1016/j.hkjot.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Effectiveness of Tai Chi Exercise in Individuals with Parkinson's Disease from 2003 to 2013*

Abstract: Objective/Background: This study aims to review the current evidence on the effectiveness of Tai Chi exercise in individuals with Parkinson's disease (PD) in the past 10 years. Methods: A systematic review of studies published in English from 2003 to 2013, retrieved from three electronic databasesdMEDLINE, Cumulative Index to Nursing and Allied Health Literature, and ScienceDirectdwas performed. The review selected only those studies that investigated the effects of Tai Chi exercise on individuals with PD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 44 publications
0
7
2
Order By: Relevance
“…Our main findings are different from the previous reviews [ 22 , 23 ]. Lee and colleagues conclude that the evidence is insufficient to suggest Tai Chi is an effective modality for PD [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our main findings are different from the previous reviews [ 22 , 23 ]. Lee and colleagues conclude that the evidence is insufficient to suggest Tai Chi is an effective modality for PD [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It would be probably that the objective evidence made our review different from the previous ones [5], [20], [21]. Lee and colleagues concluded that the evidence was insufficient to suggest that Tai Chi was an effective intervention for PD based on three RCTs [22]–[24], one non-RCT [25] and 3 uncontrolled clinical trials [26]–[28] published from 1997 to 2007 [5].…”
Section: Discussionmentioning
confidence: 96%
“…First, a number of prior reviews have been limited to qualitative synthesis and have not also included quantitative meta-analytical methods [63, 64]. For studies that did include meta-analysis, one in 2014 focused only on Tai Chi (excluding Qigong) and included 9 trials in quantitative synthesis (vs. 15 in the present study) [7].…”
Section: Discussionmentioning
confidence: 99%